Organoleptic test using the hedonic and descriptive methods to determine the quality of Pliek U. Issue 1 (January 2021) - Agustina, R; Fadhil, R; Mustaqimah,
Abstract: Pliek U is the most popular for Aceh's people due to its use as a traditional recipe mixed in the main food course. The quality establishment of Pliek U is mostly based on sensory tests from consumers. This study using the sensory and the organoleptic test. Certain methods used for panelists to assess Pliek U organoleptic were the hedonic or liking test and descriptive test. This research aims to determine the quality of Pliek U based on variations in the thickness of the fermentation and fermentation time using the organoleptic hedonic test and descriptive test. Verify was carried out by giving a questionnaire to the panelists with parameters, including; color, aroma, and taste. Furthermore, for the hedonic organoleptic, the panelists were given a questionnaire with a scale or score, i.e., 1 (most dislike), 2 (dislike), 3 (neutral), 4 (like), and 5 (most like). In comparison, the panelist descriptive test represents and identifies quality in Pliek U based on taste. For the hedonic and descriptive organoleptic test, the panelists liked the Pliek U for fermented to 7 days with a pile thickness of 30 cm, wherein the Pliek U was light brown, had a non-rancid aroma, and a sour taste. The regression analysis showed the thickness of the rasp coconut pile, and the fermentation time was significant on the level of panelist admission of the Pliek U color, and no significant effect on the aroma and taste of Pliek U.